Kan ett vinklat narrativ påverka minnesbilden? En kvantitativ studie om framing-effekt - Alrenius,Matilda; Kvist,Felicia (2025)
The aim of this study was to investigate the influence of the framing effect on individuals’ perceptions and memory of a violent event, focusing specifically on the actions of security guards. In a quantitative experimental design, the participants (n=63) were assigned either a neutral (n=30) or a biased narrative (n=33) before watching a video of a group conflict. Participants were then asked to answer questions about both central and peripheral details of the event. The results support the hypothesis that indicated that the biased narrative could negatively affect perceptions of security guards, as participants exposed to the negatively framed narrative rated the guards’ actions as more violent. That narrative led to a more negative perception of the security guards, supporting the hypothesis that the framing effect influences perception and interpretation. Gender had no significant influence on the outcomes. No significant difference was found between the groups regarding memory of peripheral details, such as the weather or the number of civilians involved. One possible explanation is that the participants’ attention was drawn to the emotionally charged central aspects of the event, which affected the answers and made both groups answer alike, which aligns with previous research on memory and perception. Various possible explanations for the results were discussed along with the study's limitations in the discussion. The study highlights the framing effect’s potential to shape how events are perceived and stored in memory.
Keywords: framing effect; memory; narrative; perception; security guards; framing-effekt; minnesbild; narrativ; ordningsvakter